Perception of health state and the use of vignettes to calibrate for socioeconomic status: results of the World Health Survey in Brazil, 2003 Percepção do estado de saúde e o uso de vinhetas para calibração por nível sócio-econômico: resultados da Pesquisa Mundial de Saúde no Brasil, 2003 - Giseli Nogueira Damacena; Mauricio Teixeira Leite de Vasconcellos; Célia Landmann Szwarcwald (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
As part of the World Health Organization (WHO) project focused on assessing the performance of national health systems, the World Health Survey (WHS) was carried out in many member countries. In order to enable comparison of self-rated health between different cultures of the same country or between different nations, the WHS questionnaire included vignettes of sample cases, that is, hypothetical stories that describe the health problems of third parties. The objective of the present study is to evaluate the possibility of using vignette ratings to implement a socioeconomic calibration scale for self-rated health in Brazil. Using Brazilian WHS data, perceptions of state of health, measured through two different strategies (self-rating and vignette-rating), were compared. The effects of socioeconomic status (educational level and number of household assets) on health domain ratings were estimated via multiple regression models, controlled for age and sex. The effects of socioeconomic status were significant for the majority of health domains in the case of self-perception, but statistically null in the case of third party ratings. It is concluded that the WHO vignettes are not appropriate for calibrating self-rated health measures in Brazil. Como parte do projeto da Organização Mundial da Saúde (OMS) de avaliação de desempenho dos sistemas de saúde das nações, a Pesquisa Mundial de Saúde (PMS) foi realizada em vários países membros. Para possibilitar a comparação de estimativas de auto-avaliação do estado de saúde coletadas entre culturas distintas, a OMS utilizou a estratégia de incluir vinhetas de casos-padrão, estórias hipotéticas que descrevem problemas de saúde de terceiros. Utilizando os dados da PMS brasileira, objetivou-se, neste trabalho, avaliar a utilização de vinhetas de casos-padrão para calibração da percepção de saúde por nível sócio-econômico. Na análise estatística foram comparadas as médias de avaliação de cada domínio por estratégia de mensuração (auto-avaliação e vinhetas) segundo sexo, faixa etária, e nível sócio-econômico (grau de escolaridade e número de bens no domicílio). Os efeitos do nível sócio-econômico sobre as avaliações dos domínios de saúde foram estimados por regressão múltipla, controlando-se por idade e sexo. No caso da auto-avaliação, os efeitos do nível sócio-econômico foram significativos para a maioria dos domínios, mas estatisticamente nulos, no caso de vinhetas. Conclui-se que a utilização das vinhetas propostas pela OMS para calibração das medidas de auto-reporte não se mostrou apropriada no caso do Brasil.